Pathways to secure food production: Structural inequalities at village levels in Yogyakarta - Putri M, Mustika; Purwa, Taly (Jurnal Ekonomi Indonesia, 2025)
This study measures Food Production Security (FPS) at the village level in DI Yogyakarta across quantity, quality, structure, and ecology dimensions, and analyzes the role of resources, technology, and institutional capacity in supporting food production. Using an Entropy-Weighted TOPSIS approach, complemented by GeoAI modeling and Mixed Geographically Weighted Regression (MGWR), results show higher FPS scores in urban areas, reflecting structural disparities in production inputs and infrastructure access. FPS is generally positively correlated with the Food Security Index (FSI), yet misalignments signal dual aspects of food security. Spatial analysis highlights heterogeneous and dual-direction effects of capital, technology, climate, and environmental management factors, emphasizing the need for spatial-based policies. Collaborative strategies combining modern agricultural technologies, targeted extension services, and optimized use of organic fertilizers and waste recycling demonstrate potential for sustainable improvement of FPS at village and sub-district levels.